Putting Searchers into Search - Dumais, Susan (Athena Lecture at SIGIR 2014, 2014)
Over the last two decades the information retrieval landscape has changed dramatically. Twenty years ago, there were fewer than 3k web sites and the earliest web search engines indexed approximately 50k pages. Today, search engines index billions of web pages, images, videos, news, music, social media, books, etc., and have become the main entry point for a wide range of information, services, communications and entertainment. Despite these tremendous accomplishments, we still have a long way to go. Many searches are unsuccessful, and even those that succeed are often harder than they should be. To address these challenges we need to extend our evaluation methods to handle the diversity of searchers, tasks, and interactivity that characterize information systems today. I will discuss recent work on user modeling and temporal dynamics of information systems to illustrate the power of utilizing converging lines of evidence from laboratory, panel, and large-scale log techniques to understand and support searchers.